The Contribution of Tourism Industry on the GDP of Western Balkan Countries - Čerović, Slobodan; Knežević, Miroslav; Matović, Vladimir; Brdar, Ivana (Industrija, 2015)
Tourism industry records various economic, social, political and others influences and provides itself important position in the overall economic development of many countries. The analysis of the available data of tourist arrivals and number of tourist overnight stays in observed countries of the Western Balkans (Serbia, Macedonia, Montenegro) led us to conduct the survey of the contribution of the tourism industry in creating GDP. Results of multivariate panel regression model (Schwarz's Bayesian Criterion) showed that tourism, due to the continued increase of the number of foreign tourists has a significant contribution to overall economic growth of the countries of the Western Balkans. The level of tourism's contribution to economic growth in the surveyed countries is different and significantly related to the diversity and quality of supply (the largest contribution to the economic growth of tourism is observed in Montenegro and the lowest in Macedonia).
Keywords: Economic Growth; Tourism; Western Balkans; GDP; Economic impact; Tourism industry